Pengaruh jenis pelarut pada ekstrak daun kelor (Moringa oleifera) terhadap mortalitas larva Aedes aegypti - Restiani Sih Harsanti; Ratna Mustika Yasi (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2019)
Innovation is needed using alternative ingredients as natural larvacide instead of temefos. One of the plants that can be used for making natural larvacide is Moringa (Moringa oleifera) which contains alkaloids and flavonoids. This study aims to determine the effect of the type of solvent on Moringa (M. oleifera) extract on the mortality of Aedes aegypti larvae and determine the most effective solvent in extracting Moringa leaves as A. aegypti larvacide. This study uses a completely randomized design with 5 replications. Moringa leaf extract is obtained by maceration with aquades, ethanol, methanol, ethyl acetate, and n-hexane. Moringa leaf extracts were tested for phytochemistry and larvacidal power was tested for A. aegypti larvae. Mortality data were analyzed by ANOVA and Tukey tests. The results showed that the type of solvent in moringa leaf extract (M. oleifera) did not significantly influence the mortality of A. aegypti larvae and the most effective type of solvent for extraction of Moringa leaves were aquades and ethanol. Based on the research findings it can be concluded that the type of solvent in moringa leaf extract does not significantly influence the mortality of A. aegypti larvae. However, the most effective types of solvents for extraction of Moringa leaves are aquades and ethanol.